Design of ultrahigh-speed low-voltage CMOS CML buffers and latches. - Heydari, P. (IEEE Transactions on VLSI systems)
A comprehensive study of ultrahigh-speed current-mode logic (CML) buffers along with the design of novel regenerative CML latches will be illustrated. First, a new design procedure to systematically design a chain of tapered CML buffers is proposed. Next, two new high-speed regenerative latch circuits capable of operating at ultrahigh-speed data rates will be introduced. Experimental results show a higher performance for the new latch architectures compared to the conventional CML latch circuit at ultrahigh-frequencies. It is also shown, both through the experiments and by using efficient analytical models, why CML buffers are better than CMOS inverters in high-speed low-voltage applications.